Microwave synthesis of calcium bismuth niobate thin films obtained by the polymeric precursor method - Simoes, A. Z.; Ramirez, M. A.; Ries, A.; Wang, F.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2006)
The crystal structure, surface morphology and electrical properties of layered perovskite calcium bismuth niobate thin films (CaBi2Nb2O9-CBN) deposited on platinum coated silicon substrates by the polymeric precursor method have been investigated. The films were crystallized in a domestic microwave and in a conventional furnace. X-ray diffraction and atomic force microscopy analysis confirms that the crystallinity and morphology of the films are affected by the different annealing routes. Ferroelectric properties of the films were determined with remanent polarization P-r and a drive voltage V-c of 4.2 mu C/cm(2) and 1.7 V for the film annealed in the conventional furnace and 1.0 mu C/cm(2) and 4.0 V for the film annealed in microwave furnace, respectively. A slight decay after 10(8) polarization cycles was observed for the films annealed in the microwave furnace indicating a reduction of the domain wall mobility after interaction of the microwave energy with the bottom electrode. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: thin films; X-ray diffraction; ferroelectricity